Samuel Beckett e os limites do in-dizível - Maciel, Ulisses Augusto Guimarães (2016)
The novels Molloy, Malone Dies and The unnamable, trace the path of Samuel Beckett in the composition of a narrative known for challenging the limits of representation, highlighting the precariousness of thought which fails in its attempt to grasp reality. In this context, considering the representativeness a game that comes from inarticulable chaos, we used the concepts of reality, language, and translation addressed by the Czech-Brazilian philosopher, Vilém Flusser and the existentialist philosophy of Martin Heidegger and Albert Camus, in an attempt to show the imprecise nature of Beckett works, before the word impossibility, constant trial and failure in the face of the un-speakable.